Criminological Analysis of Green Delicts in the Federal District of Brazil - Ribeiro, Renata Esteves; Corrêa, Rodrigo Studart; Couto Júnior (In Memoriam), Antônio Felipe (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
Green criminology studies transgressions that cause damage to the natural environment. Spatial approaches deal with incidental conditions of every sort of crime, and they are particularly appropriate to unveil rational components of criminal activities. In the Brazilian scenario, previous studies have pointed to the need for law enforcement and further studies on green criminology. This work aimed to unveil spatial patterns of environmental crimes in the Federal District of Brazil (FDB) and their possible causes. Records of environmental crimes from 2009 to 2016 registered by the local police were subject to spatial statistics, and results showed that most occurred in urban areas. Brasília City and its surrounding counties, farms, legally protected areas, and natural habitats create a mosaic of land uses that have influenced the spatial distribution of environmental crimes recorded by the local police. Over the years, crimes have occurred repeatedly in similar areas, suggesting sensitive places for their commitment. Still, those areas were not restricted to the neighborhood boundaries, and the homogeneity among contiguous neighborhoods supported similar levels of disorder. The proximity of these places to legally protected areas, the permeability phenomenon, and some types of land use have been identified as possible explanations for those crime records.